2021
DOI: 10.2196/27609
|View full text |Cite
|
Sign up to set email alerts
|

Notes from the Field: The Combined Effects of Tocilizumab and Remdesivir in a Patient with Severe COVID-19 and Cytokine Release Syndrome

Abstract: SARS-CoV-2 is known to cause severe bilateral pneumonia and acute respiratory distress syndrome or COVID-19 in patients, which can be debilitating and even fatal. With no drugs or vaccines available yet, a wide range of treatment regimens used are being repurposed. The need of the hour is to analyze various currently available regimens and devise a treatment plan that is most effective for COVID-19. Here we describe the case of a 68-year-old man with hypertension and diabetes, exhibiting symptoms of cough and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Additional treatment with a course of dexamethasone or equivalent is further recommended. One patient with a SARS-CoV-2-induced cytokine release syndrome was successfully treated with a combination of tocilizumab and remdesivir [29]. Initial studies showed conflicting results and no significant difference in mortality or clinical status between tocilizumab-treated and placebo groups.…”
Section: Tocilizumabmentioning
confidence: 99%
“…Additional treatment with a course of dexamethasone or equivalent is further recommended. One patient with a SARS-CoV-2-induced cytokine release syndrome was successfully treated with a combination of tocilizumab and remdesivir [29]. Initial studies showed conflicting results and no significant difference in mortality or clinical status between tocilizumab-treated and placebo groups.…”
Section: Tocilizumabmentioning
confidence: 99%
“…In this condition, remdesivir monotherapy is frequently ineffective, but the combination of remdesivir with antibody-based therapeutics holds promise. Remdesivir, combined with tocilizumab (an anti-interleukin-6 monoclonal antibody) and dexamethasone, was administered at the early stage of the disease, resulting in timely resolution of the cytokine storm and subsequent improvement in ARDS symptoms and eventual recovery [155]. Combination of remdesivir with convalescent plasma or anti-SARS-CoV-2 monoclonal antibodies (mAbs) achieved high viral clearance [156,157].…”
Section: Combination Therapy With Biomacromolecule and Small Moleculementioning
confidence: 99%